The widely used Ucp1-Cre transgene elicits complex developmental and metabolic phenotypes - Manasi Suchit Halurkar; Oto Inoue; Archana Singh; Rajib Mukherjee; Meghana Ginugu; Christopher Ahn; Christian Louis Bonatto Paese; Molly Duszynski; Samantha A. Brugmann; Hee-Woong Lim; Joan Sanchez-Gurmaches (Nature Communications)
Abstract Bacterial artificial chromosome transgenic models, including most Cre-recombinases, enable potent interrogation of gene function in vivo but require rigorous validation as limitations emerge. Due to its high relevance to metabolic studies, we perform comprehensive analysis of the Ucp1-Cre Evdr line which is widely used for brown fat research. Hemizygotes exhibit major brown and white fat transcriptomic dysregulation, indicating potential altered tissue function. Ucp1-Cre Evdr homozygotes also show high mortality, tissue specific growth defects, and craniofacial abnormalities. Mapping the transgene insertion site reveals insertion in chromosome 1 accompanied by large genomic alterations disrupting several genes expressed in a range of tissues. Notably, Ucp1-Cre Evdr transgene retains an extra Ucp1 gene copy that may be highly expressed under high thermogenic burden. Our multi-faceted analysis highlights a complex phenotype arising from the presence of the Ucp1-Cre Evdr transgene independently of intended genetic manipulations. Overall, comprehensive validation of transgenic mice is imperative to maximize discovery while mitigating unexpected, off-target effects.